Régimen de propiedad horizontal en Colombia: estudio del alcance de la Ley 675 de 2001 y su eficacia frente a la relación entre copropietarios y administrador a 2016 - Acevedo Orrego, Uriel Cristóbal (Derecho, Ciencias Jurídicas y Políticas, 2017)
With the porpuse to achieve a peaceful coexistence within owners, and within owners and buildings and residencial houses´ administrators; this article is an academic product that identify the obligations and rights, faculties and limits of this subjects that are involved in the coexistence and management of this kind of properties insides the special form of regulation knows as “Propiedad horizontal”. Also, it is important that each one – owners and administrators- be advised about the obligations and rigths they have as well.